THE ROLE OF CRITICAL READING STRATEGIES IN TEACHING ENGLISH (Multidisciplinary Journal of Science and Technology, 2024)
This articles discusses and summaries a number of reading strategies that helps language learners how read texts and analyze them critically, and suggests some useful strategies to improve reading comprehension.